Hubungan Durasi Kerja dan Sikap Kerja Dengan Keluhan Nyeri Leher pada Pekerja Panen Kelapa Sawit di Desa Tepian Baru KM. 110 Kecamatan Bengalon, Kabupaten Kutai Timur - Rahmatullah, Istiarto; Rahmatullah, Ilham Rahmatullah; Sulung Alfianto Akbar; Rahmatullah, Laurentius Gae (Journal of Mandalika Literature, 2024)
Background: Research on oil palm harvesters consistently shows a high prevalence of musculoskeletal disorders (MSD) with Neck Paint disorders (neck pain complaints) due to unergonomic working posture and repetitive manual work (M. Sultan et al., 2022; Rizki Asih Gustara & S. Susilawati, 2023; Vira Teresia & D. Lestari, 2022). A study using the Rapid Whole Body Assessment (REBA) questionnaire and Nordic Body Map revealed that most workers are at moderate to high risk of MSD, with common complaints in the right shoulder, left and right legs, and lower back (M. Sultan et al., 2022; Vira Teresia & D. Lestari, 2022). Factors contributing to MSD include personal characteristics (e.g., age, work experience), employment factors (e.g., work posture, workload, repetitive movements), and environmental conditions (Rizki Asih Gustara & S. Susilawati, 2023). A significant correlation between work posture and musculoskeletal complaints has been observed (Vira Teresia & D. Lestari, 2022). To mitigate this problem, the researchers recommend that workers adopt more ergonomic postures and employers implement interventions to reduce the risk of MSD (M. Sultan et al., 2022). Objective: to determine the relationship between work duration and work attitude with neck pain complaints in oil palm harvester workers in Tepian Baru Village, Km 110, Bengalon District, East Kutai Regency. Research Method: The research method is quantitative using a cross secional approach. The population of oil palm harvesting workers in Tepian Baru Village is 106 people. The sample technique used is purposive sampling technique with the Slovin formula used to find the sample size, the sample size in this study is 84 samples, and data analysis using Chi-Square. Results: The results of this study showed a relationship between work duration (p-value : 0.009), work attitude (p-value : 0.029) and neck pain complaints in oil palm harvester workers in Tepian Baru Village, Km 110, Bengalon District, East Kutai Regency. Conclusion: There is a relationship between work duration and work attitude and neck pain complaints in oil palm harvester workers in Tepian Baru Village, Km 110, Bengalon District, East Kutai Regency.